Evaluation of Shear Bond Strength of Resin-Based Composites to Biodentine with Three Types of Seventh-Generation Bonding Agents: An In Vitro Study - Huda Abbas Abdullah; Zahraa Abdulaali Al-Ibraheemi; Zanbaq Azeez Hanoon; Julfikar Haider (International Journal of Dentistry)
Background and Aim. Biodentine refers to a bioactive material commonly applied for dental restoration in clinical practice, but poor adhesion of the Biodentine to the restorative materials could affect the quality and long-term integrity of the final restoration. The study aimed to assess shear bond strength (SBS) of two resin-based composites to Biodentine using three commercially available 7th generation bonding agents. Methods. Forty-eight acrylic blocks having central holes with a nominal diameter of 4 mm and a depth of 2 mm were prepared. The holes of the acrylic blocks were filled with Biodentine, which was prepared following the guidelines provided by the manufacturer. Then, the specimens were divided into six groups (n = 8). Groups 1, 2, and 3, Tetric N-Ceram composite bonded to Biodentine with Tetric N-bond, Xeno V+, Bond Force bond, respectively. Group 4, 5, and 6, Filtek Z350 bonded to Biodentine with the same three adhesives. The specimens were placed in distilled water for 24 hours and tested for the SBS in a universal testing machine at a crosshead speed of 1 mm/min. The test data were listed in a table and independent samples t-test and analysis of variance (ANOVA) were conducted as a part of the statistical analysis. Results. The Tetric N bonding agent achieved the highest SBS followed by Bond Force, and Xeno V and highly significant difference was found. On the other hand, an overall increase in the SBS values of the Tetric N-Ceram resin was noticed in comparison with the Filtek Z350 and the differences was statistically significant. Although the specimens failed in adhesive, cohesive and mixed fracture modes but the cohesive was found to be the dominant failure mode in all groups. Conclusion. Among the tested bonding agents and resin composites, the Tetric N-Ceram composite bonded by Tetric N-bond self-etch adhesive with the Biodentine showed the highest SBS compared to the other combinations.